Psychological stress of parents of preterm infants enrolled in an early discharge programme from the neonatal intensive care unit: a prospective randomised trial. Issue 2 (17th July 2008) - Sáenz, P; Cerdá, M; Díaz, J L; Yi, P; Gorba, M; Boronat, N; Barreto, P; Vento, M
Abstract : Background: Psychological stress of parents of preterm infants is aggravated by prolonged hospitalisation. Early discharge programmes (EDPs) have been implemented to alleviate this situation. Objective: To evaluate parental psychological stress in an EDP for the first 3 months after neonatal intensive care unit (NICU) discharge. Design/methods: Prospective randomised trial comparing parents of preterm infants assigned to EDP (n = 72) or standard discharge programme (SDP) (standard discharge) (n = 68). At discharge, parents were evaluated using the Hospital Anxiety and Depression Scale (HAD), and the Likert Scale for well-being every 10 days for 3 months. Parental narrative of Worrying and Helping issues was assessed using a semi-structured interview. Results: Length of stay was greater in the SDP group (p<0.01). HAD showed no differences in anxiety, but SDP mothers scored higher in depression (p<0.05). Altogether, parents reported a worrisome emotional condition (EDP 87.2%; SDP 80%), which decreased at the end of the study (EDP 45.2%; SDP 34.5%). Their baby's physical well-being was the most relevant issue in the narrative for Worrying and Helping issues at discharge (EDP 69.2%; SDP 67.5%); however, it decreased at the end of the study (EDP 22.6%; SDP 24.1%). At discharge, the paediatrician's support was more for the SDP group. No differences on the Well-Being Scale were found, but the EDP group always scored better. Conclusions: Vulnerability of parents enrolled in an EDP did not increase after hospital discharge. Physical well-being of the baby was the most important issue for both groups. EDP parents requested less paediatric support and scored higher in the Well-being verbatim. Trial registration number: Registered at the Clinical Trial Government Protocol Registration System no NCT00569608.